Intralipid fails to rescue bupivacaine-induced cardiotoxicity in late-pregnant rats - Sherman, Caitlin; Koons, Natalie; Zargari, Michael; Cha, Catherine; Hirsch, Jason; Hong, Richard; Eghbali, Mansoureh; Umar, Soban (Frontiers in Medicine, 2022)
Background: Females routinely receive bupivacaine for obstetric and regional anesthesia. An accidental overdose of bupivacaine can result in cardiotoxicity and cardiac arrest. Intralipid (ILP) rescues bupivacaine-induced cardiotoxicity in male rats. However, bupivacaine cardiotoxicity and ILP rescue have not been studied in non-pregnant and late-pregnant female rats. Here, we tested the hypothesis that an appropriate dose of ILP would rescue non-pregnant and late-pregnant rats from bupivacaine-induced cardiotoxicity. Methods: Non-pregnant (n=6) and late-pregnant (n=7) female rats received intravenous bupivacaine (10-mg/kg bolus) to induce asystole. Resuscitation with 20% ILP (5-ml/kg actual body weight, single bolus, and 0.5-ml/kg/min maintenance) and chest compressions were continued for 10-minutes. Serial heart rate (HR), left ventricular ejection-fraction (LVEF%), and LV-fractional shortening (LVFS%) were recorded at baseline and 10-min after bupivacaine-induced cardiac arrest. Data are meanSD followed by 95% CI. P-values <0.05 were considered statistically significant. Results: All rats developed cardiac arrest within a few seconds after bupivacaine. All non-pregnant rats were successfully rescued by ILP, with a HR of 280+/-32 bpm at baseline vs. 212+/-18 bpm at 10-min post ILP (p<0.01), LVEF of 70+/-6% vs. 68+/-5% (p=ns), and LVFS of 41+/-5% vs. 39+/-4% (p=ns). Interestingly, 6 out of 7 late-pregnant rats did not recover with ILP. Baseline HR, LVEF and LVFS for late-pregnant rats were 330+/-40 bpm, 66+/-5% and 38+/-4%, respectively. At 10-min post ILP, the HR, LVEF, and LVFS were 39+/-102 bpm (p<0.0001), 8+/-22% (p<0.0001), and 5+/-12% (p<0.001), respectively. Conclusions: ILP successfully rescued bupivacaine-induced cardiac arrest in non-pregnant rats, but failed to rescue late-pregnant rats.